Lived Faith and Moral-Spiritual Development in Muslim Early Childhood: A PRISMA-Based Systematic Review and a Proposed Multi-Level Assessment Framework - Fauziah, Yanuar Rizki; Murfi, Ali; Syafii, Ahmad; Prasetyo, Gatot (Al-Athfal: Jurnal Pendidikan Anak, 2026)
Purpose – This review maps evidence for assessing lived faith and moral-spiritual development among children aged 0-8 years, particularly in culturally grounded Muslim settings, and proposes a multi-level framework for future instrument development.Design/methods/approach – A systematic review was reported using PRISMA 2020 and followed by integrative conceptual synthesis. Scopus, Web of Science, PsycINFO, and ERIC were searched, supplemented by backward reference searching. Of 680 records, 51 studies published in 2020-2025 were included and classified by their primary evidential role; supplementary theoretical and methodological sources were excluded from the review denominator.Findings – Two studies provided direct instrument-development evidence: a parent-rated faith scale for preschool children and a spiritual-values scale for primary-school children. Other studies addressed indicator conceptualization and cultural transfer (n = 10), lived faith ecology and religious socialization (n = 11), moral-prosocial development and self-regulation (n = 8), and pedagogy, programs, and policy (n = 20). The evidence is stronger for defining construct boundaries, candidate domains, and adaptation procedures than for recommending a ready-to-use instrument. Prosociality and self-regulation are proximal outcomes, not direct evidence of lived faith unless linked to faith-related meaning and socialization.Research implications/limitations – The framework is a conceptual and methodological agenda, not a validated instrument. Generalization is limited by scarce direct measurement evidence, few explicitly Muslim early-childhood studies, heterogeneous constructs and populations, incomplete retained search records, and the absence of cross-group invariance and reportable inter-rater agreement.Practical implications – The framework supports construct co-design, cognitive interviewing, age-sensitive reports, structured observation, simple vignettes, and staged psychometric validation while separating child behavior, faith-related meaning, and religious socialization ecology.Originality/value – The article links Islamic and local construct grounding with developmental operationalization and iterative cultural-psychometric validation, providing a transparent design logic for culturally responsive assessment rather than a universal scale.Paper type Literature review